1996 Olympic Games in Atlanta: The best male volleyball-teams: Part 1 Netherlands - Fröhner, B. (The Coach, 1996)
This report is the first in a series which aimes to pinpoint the characteristics and profile of requirements for top-class volleyball and identify ways in which young volleyball players can be led to acquire the skills and capabilities associated with them. Berthold Fröhner highlights some typical features, key areas of performance and errors commited by the best teams in the tournament.